O autor em cena : uma investigação sobre a autoria e seu funcionamento na modernidade - Marco Antônio Sousa Alves (2014)
Consider the following picture: the author as the owner of her work. It is so trivial that we tend to think of it as having always existed, perhaps under different disguises. But the author and her work are much more contingent and unstable than they seem to be. The following questions then come forth: when did this figure emerge, and how does it work? How is the subject related to the discourse, so that it is given an authorial unit? And since when has it become conceivable that a discourse can be attributed to an individual and it can be owned by someone? To a certain extent, my aim here is to answer these questions from a Foucauldian perspective, according to which the modern author is conceived, at the same time, as a way of organizing the discourse, a certain specification of the subject-function, and a complex mechanism of power. This dissertation is structured in three parts: (1) an initial study of Foucault's notion of “author” that aims at providing the needed elements for the investigation to come; (2) a short analysis of the author-function and of the relationship between author, discourse, subject, and power, which is then followed by a methodological survey that aims to establish the basic guidelines of a genealogical approach; (3) a short genealogy of the author in modernity. In this last part, even though the main focus of my dissertation is the emergence of the author as the owner of her work, I find it necessary to take into account a broader historical period, so that I can analyze how the complex and multifaceted author-function has operated in modernity, and how the author has acquired authority and assumed responsibilities until she could finally become the owner of her work. In short, I consider three historical stages. First, the emergence of the author as auctoritas, in association with some changes in the writing culture, in the fourteenth and fifteenth centuries. Secondly, the emergence of the author as a transgressor, who is responsible for her creations, in association with the development of the press, the censorship, and the new forms of controlling and consecrating the author, which occurred in the sixteenth and seventeenth centuries. Finally, the emergence of the author as the owner, in association with some changes in the law, the literary system, the book market, and in aesthetic and moral discourses, in the eighteenth century. Even though this dissertation may seem, at a first glance, a long and distant historical study, far removed from current issues, I believe that this "return to the past" is called for by the “urgencies of the present". We witness now the emergence of new subject-positions and new technologies of power, which seem to indicate new forms of unifying and appropriating discourses, which are now understood as a huge, shared and ever-changing information network. This dissertation, to some extent, is intended to be a historical and philosophical analysis that encompasses a critical attitude, understood here as a transforming exercise, i.e., an activity that changes our way of being and allows us to think and act differently.